2016
DOI: 10.1039/c6ra06298a
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-promoted titania as solid acid for catalytic hydrolysis of waste bottle PET in supercritical CO2

Abstract: Tungsten-promoted titania solid acid catalysts were synthesized by a hydrothermal method and used in the hydrolysis of waste bottle polyethylene terephthalate (PET) in supercritical CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
(72 reference statements)
2
22
0
Order By: Relevance
“…The use of WO 3 -based catalyst for pollutant remediation in liquid phase mainly concerns the oxidation of organic compounds via photocatalytic processes. Only a few recent studies have dealt with WO 3 -based catalysts for non-photocatalytic application, such as H 2 O 2 electrogeneration over WO 2.72 /Vulcan XC72 gas diffusion electrode [349], hydrolysis of waste bottle PET in supercritical CO 2 assisted by acidic catalysis over WO 3 -TiO 2 [350] or heavy metal ion adsorption on inorganic-organic hybrid WO x -ethylenediamine nanowires [351]. However, this section is focused on the main use of tungsten-based catalysts in liquid phase, namely photocatalysis.…”
Section: Pollutant Remediation In Liquid Phase (Photocatalysis)mentioning
confidence: 99%
“…The use of WO 3 -based catalyst for pollutant remediation in liquid phase mainly concerns the oxidation of organic compounds via photocatalytic processes. Only a few recent studies have dealt with WO 3 -based catalysts for non-photocatalytic application, such as H 2 O 2 electrogeneration over WO 2.72 /Vulcan XC72 gas diffusion electrode [349], hydrolysis of waste bottle PET in supercritical CO 2 assisted by acidic catalysis over WO 3 -TiO 2 [350] or heavy metal ion adsorption on inorganic-organic hybrid WO x -ethylenediamine nanowires [351]. However, this section is focused on the main use of tungsten-based catalysts in liquid phase, namely photocatalysis.…”
Section: Pollutant Remediation In Liquid Phase (Photocatalysis)mentioning
confidence: 99%
“…For instance, Guo et al developed a tungsten-promoted titania solid acid catalyst system that can be reused five times without noticeable performance loss. 19 Kang et al reported that ZSM-5-based zeolites can be easily recycled for waste PET hydrolysis. 6 Unfortunately, these technologies still face several restrictions that hinder their industrialization: (1) these catalysts have relatively low catalytic activity, and severe reaction conditions are required for achieving efficient hydrolysis of PET; (2) the separation of the solid catalyst from the product (TPA) requires alkali dissolution and acid precipitation, which inevitably produces a large amount of saline wastewater and increases the production costs.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical recovery methods of PET depolymerization usually include hydrolysis, methanolysis and glycolysis, among others 10,11 . The reaction temperature and pressure of hydrolysis are too high, and the obtained monomers need to be crystallized many times before they can be directly used in the synthesis of PET 12‐15 . Glycolysis has been widely studied, but monomer recovery is relatively low even in the presence of catalysts 16‐18 .…”
Section: Introductionmentioning
confidence: 99%